Creativity in construction project through entrepreneurial leadership, innovative ambidexterity and collaborative culture - Khairuddin, S.; Haider, S. A.; Tehseen, Shehnaz *; Iqbald, S. (Union of researchers of Macadonia, 2021)
The purpose of this paper is to empirically find out how entreprene-\\urial leadership impacts the creativity in projects and the way innovation ambidexterity acts as a mediator and collaborative culture as moderator in the process. The non-probability random sampling technique and time lag was used to collect data from 300 employees working at project-based construction companies of Pakistan. Smart PLS SEM v.3.2.8 was used to test the hypotheses. The result indicates that entrepreneurial leadership has a significant and positive impact on creativity in projects. Entrepreneurial leaders act as a risk taker and encourage novelty, therefore, enhance innovation ambidexterity in the organization which in turn results creativity in projects. However, results indicate collaborative culture does not play significant role as moderator on the relationship between entrepreneurial leadership and creativity in projects.